2017
DOI: 10.1177/0731684417693428
|View full text |Cite
|
Sign up to set email alerts
|

Studies on flax-polypropylene based low-twist hybrid yarns for thermoplastic composite reinforcement

Abstract: In this present study, thermally treated flax–polypropylene (PP) based hybrid yarns have been manufactured using DREF-3 spinning method for thermoplastic composite reinforcement. The effect of different process parameters such as core yarn twist level, sheath ratio and thermal treatment temperature on hybrid yarn properties has been studied thoroughly using Box–Behnken design. The DREF-3 spun hybrid yarn for composite reinforcement is optimized based on weavability performance, tensile behaviour and flexural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Further details on the structure of the natural fibre/thermoplastic fibre hybrid yarn and the weaving process using wrap spinning method were given by Baghaei et al [12] and Zhang and Miao [13]. The main advantage of hybrid yarns containing both matrix and reinforcing components in its structure is that the commingled structure improves the impregnation efficiency by the thermoplastic resin during composite manufacturing due to the lowest effective resin flow distance [14,15]. This was confirmed by Kannan et al [16] who observed that the interwoven fabric structures provide shorter resin flow time and good matrix impregnation compared to other possible preforms.…”
Section: Manufacturing Of Flax/pp Biocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further details on the structure of the natural fibre/thermoplastic fibre hybrid yarn and the weaving process using wrap spinning method were given by Baghaei et al [12] and Zhang and Miao [13]. The main advantage of hybrid yarns containing both matrix and reinforcing components in its structure is that the commingled structure improves the impregnation efficiency by the thermoplastic resin during composite manufacturing due to the lowest effective resin flow distance [14,15]. This was confirmed by Kannan et al [16] who observed that the interwoven fabric structures provide shorter resin flow time and good matrix impregnation compared to other possible preforms.…”
Section: Manufacturing Of Flax/pp Biocompositesmentioning
confidence: 99%
“…A porosity fraction lower than 3.9% (3.4% when accounting for fibre degradation) was obtained for all conditions with a minimum porosity fraction of 1.1% (0.6% when accounting for fibre degradation) observed for processing at 200°C under 40 bar during 10 min. Those relatively low values of overall porosity may be attributed to the thorough mixing between the flax and PP fibres inside the commingled yarns [13,14,16], and the resulting good impregnation during manufacturing. Fig.…”
Section: Microstructural Analysis Of Flax/pp Biocompositesmentioning
confidence: 99%
“…In these hybrid yarns, the reinforcing components based on natural fibres form the core of the structure and thermoplastic polymers are wrapped (by wrapping, micro-braiding or DREF-spinning) over the core flax yarn. Bar et al [156] [157] have used this technology with Flax/PP materials. These commingled yarns with thermoplastic polymers improve the quality of impregnation of the composite material during the thermo-compression step.…”
Section: Cohesion By Wrapping/comingling/micro-braidingmentioning
confidence: 99%
“…Then again when it comes to natural fiber reinforced thermoplastic composites, yarn twist restricts the polymer penetration into the reinforcing fiber bundles . This lead to composite with lot of voids and ultimately a composite with inferior mechanical properties . Hybrid yarn is a yarn, which contains both the matrix forming and reinforcing components in its structure.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies on wrap spun yarn compressed composites explain the effect of wrap spun yarn structure and flax content on their composite properties but do not consider the effect of level of flax/PP fiber mixing in the wrap yarn structure. Moreover, in the process of woven fabric formation, wrap spun yarns are not suitable as warp and even as a weft in high‐speed weaving due to their poor mechanical behavior . Thermally bonded yarns have very good potential as composite reinforcing component but the existing thermally bonded yarns/rovings are not suitable for textile preforming.…”
Section: Introductionmentioning
confidence: 99%